Filipiniana book guild series I (National Commission for Culture and the Arts and the Filipinas Heritage Library, 2001)
Provides an image archive of all of the 24 volumes of the Filipiniana Book Guild Series I published between 1962 and 1976 in a searchable database based on the original table of contents and index of the books.